2020
DOI: 10.1002/cne.25082
|View full text |Cite
|
Sign up to set email alerts
|

Functional, molecular and morphological heterogeneity of superficial interneurons in the larval zebrafish tectum

Abstract: The superficial interneurons, SINs, of the zebrafish tectum, have been implicated in a range of visual functions, including size discrimination, directional selectivity, and looming‐evoked escape. This raises the question if SIN subpopulations, despite their morphological similarities and shared anatomical position in the retinotectal processing stream, carry out diverse, task‐specific functions in visual processing, or if they have simple tuning properties in common. Here we have further characterized the SIN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 71 publications
(106 reference statements)
5
10
0
Order By: Relevance
“…Three of those 13 lines were further surveyed, resulting in the identification of multiple neuronal morphologies closely resembling those previously found in the adult goldfish optic tectum 23 . Further tectal diversity studies have resulted in the characterization of previously unidentified cell types within the optic tectum, as well as cell types that corroborate previous studies in other teleosts [24][25][26][27] . These cell type diversity studies (which combine functional imaging, electrophysiological recordings, and neurotransmitter typing) together with the recent publication of a larval zebrafish brain atlas 28 constitute a wealth of knowledge surrounding the zebrafish optic tectum.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Three of those 13 lines were further surveyed, resulting in the identification of multiple neuronal morphologies closely resembling those previously found in the adult goldfish optic tectum 23 . Further tectal diversity studies have resulted in the characterization of previously unidentified cell types within the optic tectum, as well as cell types that corroborate previous studies in other teleosts [24][25][26][27] . These cell type diversity studies (which combine functional imaging, electrophysiological recordings, and neurotransmitter typing) together with the recent publication of a larval zebrafish brain atlas 28 constitute a wealth of knowledge surrounding the zebrafish optic tectum.…”
Section: Introductionsupporting
confidence: 77%
“…We found few cholinergic neurons; however, two developing populations without a known neurotransmitter identity show expression of id2b, thus we hypothesize these populations may have PyrN, TLPN, or TGPN morphologies. Superficial interneurons (SINs) have also been described as primarily GABAergic and receiving glutamatergic input directly from retinal ganglion cells 27 . Of the eight populations in our data that appear to contain mature neurons, four are GABAergic and synapse with glutamatergic neurons.…”
Section: Neuronal Cell Types In the Larval Optic Tectummentioning
confidence: 99%
“…In teleost fish, the optic tectum is the main visual processing region, it is involved in the detection and processing of visual stimuli to generate goal-directed motor behaviors such as prey capture (62). Similar to our findings in A. mexicanus, numerous cellular response types have been previously identified in the zebrafish tectum, including those which respond selectively to changes in light level (63). We identified shared cellular response types across surface and both cave populations of A. mexicanus, though the number and sensitivity of responsive cells was severely reduced across cave populations.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have identified a laminar organization of the zebrafish tectum, with different layers corresponding to distinct functional specializations (27,65,66). Numerous cellular response types have been previously identified in zebrafish, including those which respond selectively to changes in light level (63). Their identification in A. mexicanus provides an opportunity to investigate the genetic basis of tectal wiring through hybridization experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation